PERANAN PEMBELAJARAN ABAD-21 DI SEKOLAH DASAR DALAM MENCAPAI TARGET DAN TUJUAN KURIKULUM MERDEKA - Dwi Utari; Ahmad Muadin (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2023)
One of the most important and fundamental things in the world of education is the curriculum. It is inconceivable that if the curriculum is not designed properly, students will not achieve learning targets that are in accordance with their learning needs and in accordance with their respective times. Therefore, the curriculum is dynamic in adapting to the times and technology as it is today. The aim of this research is to provide information and a clear picture of 21st century learning and 4C skills in achieving the targets and goals of the independent curriculum. The approach method used in this research is a descriptive qualitative approach. Data collection uses a research approach in the form of library research. Teachers can form ideas about what and how to teach that can achieve the expected curriculum targets. The learning process in the 21st century emphasizes meaningful and student-centered learning and develops student competencies, especially 21st century skills, namely 4C skills (Critical thinking, Creative, Collaboration, Communication). Through 21st century learning that sparks 4C skills, students can help teachers achieve the targets and goals of the independent curriculum and realize the Pancasila student profile.